Understanding the outcomes of multi-centre clinical trials: a qualitative study of health professional experiences and views. - Lawton, J; Jenkins, N; Darbyshire, J; Farmer, A; Holman, R; Hallowell, N (2012)
All trials use protocols to standardize practice within and between trial centres and to enable replication of an experiment across space and time. However, while 'centre effects' have been noted in the literature, the processes and mechanisms by which trial staff convert a protocol into practice, and create 'evidence', is a relatively understudied phenomenon. We undertook a qualitative investigation of a multi-centre, UK-based, insulin trial, where differences were found between participating centres in their attainment of the trial's primary clinical endpoint (HbA(1c)), a measure of patients' average blood glucose control. In-depth interviews were conducted with 12 research nurses and nine clinicians recruited from 11 centres in 2009, and explored their views about trial participation and experiences of trial delivery from inception to closeout. Staff accounts highlighted mixed agendas and/or ambivalent views about involvement in pharmaceutically funded trials, and discursive and temporal strategies by which they attempted to separate research from clinical practice and to convert commercially funded work into better patient care. Staff in different centres also reported divergent practices by which they recruited patients into the trial and 'enacted' the protocol to enhance trial outcomes and/or to individualise and improve patient care. By exploring, and comparing, the experiences of staff who worked on the same trial but in different centres, this study highlights the importance of understanding, and exploring, the enactment of protocols in ways which situate individual practices within both local (institutional) and global contexts.